Caregiving Subsidies and Spousal Early Retirement Intentions - Joan Costa-Font; Cristina Vilaplana-Prieto (Institute of Labor Economics (IZA), 2022)
Balancing caregiving duties and work can be both financially and emotionally burdensome, especially when care is provided to a spouse at home. This paper documents that financial respite for caregivers can influence individuals' early retirement decisions. We examine the effect of a reform extending long-term care (LTC) benefits (in the form of subsidies and supports) in Spain after 2007 on caregiving spouse's early retirement intention. We subsequently examine the effect of austerity spending cuts in 2012 reducing such publicly funded benefits, and we compare the estimates to the effects of an early retirement reform among private sector workers in 2013. We document evidence of a 10pp reduction in the early retirement intentions after the LTC reform even though the effect is heterogeneous by type of benefit. Consistently, austerity spending cuts in benefits are found to weaken retirement intentions. Our estimates suggest that cuts in caregiving subsidies exert a much stronger effect on early retirement intentions than actual early retirement reforms.
Keywords: I18; J14; 330; long-term care; employment; retirement; informal care; caregiving subsidies; home care